Analisis Faktor The Brief Jail Mental Health Screen Versi Bahasa Indonesia Dengan Metode Confirmatory Factor Analysis (CFA) - Pangestu, Muhammad Aji Dimas; Muhammad, Ali (Jayapangus Press, 2022)
Prisoners with mental illness are more likely to engage in institutional violence and rule violations, especially those with psychotic or depressive symptoms. Mental health screening is an important way to identify Serious Mental Illness (SMI) of newly admitted prisoners. However, in Indonesia, health screening only focuses on physical examination, so mental health screening is overlooked. This research aims to conduct a factor analysis of the BJMHS in Indonesian version for male prisoners in Indonesia. The method used in this research is quantitative with a cross cultural adaptation approach which also displays elements of validity and reliability testing and confirmatory factor analysis (CFA). The sample collection method was purposive sampling with a characteristic, prisoners whose ages were between 18-60 years at Lapas Kelas IIB Kayuagung. This research obtained good content validity (I-CVI 1.0 and S-CVI 1.0), and satisfactory internal consistency reliability (KR20 0.771 and KR21 0.73). A good preliminary analysis (KMO 0.780 and Bartlett's Test of Sphericity p < 0.001). The coefficient of determination is above 0.3 with the goodness-of-fit value meeting the requirements (chi-square P-value = 0.001, GFI = 0.836, RMSEA = 0.072, and CFI = 0.752). The standardized estimate value both overall and for each variable is very good (0.11-0.22). The factor loading results are very good (P-value < 0.001), followed by the residual covariance results showing that each indicator variable has a relatively good matching relationship except for the PS1 and PS2 indicator variables. The Indonesian version of the Brief Jail Mental Health Screen is considered quite promising to measure the serious mental health experienced by male prisoners, but this requires further research involving more research samples in various correctional institutions and prisons in Indonesia.